Vernix caseosa peritonitis following vaginal delivery: Cheesy peritonitis - Arif Abdullah; Asri Che Jusoh; Noryani Mohd Samat; Murni Hartini Jais (Formosan Journal of Surgery, 2022)
The incidence of the acute abdomen during early postpartum is not uncommon. In this report, we highlight an extremely rare cause of acute abdomen which posed significant diagnostic and management dilemmas. In this case, the patient presented at day 5 postvaginal delivery with progressive respiratory embarrassment, mild abdominal pain, and fever. Her clinical signs, blood and laboratory parameters, and imaging (ultrasound and computed tomography scan) were however nonspecific except for worsening ascites. Laparotomy was determined as the best procedure for her in view of her polymorphonuclear cell count from an abdominal paracentesis being very high and the absence of clinical improvement even with the best intensive care support. Vernix caseosa peritonitis (VCP) was finally diagnosed based on histological examination of the “cheesy” slough extracted intraoperatively. Our case illustrates the nonspecific features of VCP which may be potentially fatal if undiagnosed early and no definitive care is provided.